GENETIC DIVERSITY AND POPULATION STRUCTURE OF COMMON BEAN GENOTYPES USING MORPHOLOGICAL TRAITS AND SSR - Shawin A. Khdir,; N. S. Ahmad,; E. O. Hama-Ali,; Sh. M. Abdullah, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The objectives of this study were to estimate the performance of the common bean (Phaseolus vulgaris L.)  genotypes under water-stress conditions, and their genetic diversity. White bean surpassed the others for relative water content, root/shoot ratio and leaf area under water-stress condition. Scatter plot indicates a strong association of yield with pod numbers plant-1, branch number and harvest index. A total of 69 polymorphic were obtained, applying 26 SSR primers on 14 genotypes. Major allele frequency was 0.601, and the average value of PIC was 0.407. The highest value of gene diversity (0.745) and PIC (0.704) were recorded for BMd-23 marker. Molecular variance among population indicated 25%, while 47% was realized within populations. Structure analysis divided the common bean genotypes into three groups (DeltaK value =3). Chity and Boschbohnen were identified to have a mixed ancestor while all the others were pure at their populations. A dendrogram and PCoA analyses are accordingly indicated three groups of the genotypes based on SSR marker data. STRUCTURE, UPGMA and PCoA analysis revealed the presence of two separated gene pools of Andean and Mesoamerican common beans, with a high level of genetic differentiation (FST value=0.250). Both phenotypic and molecular genetic outcomes here would accelerate future improvement programs.